Bridging Technology and Islamic Studies: Digital Flipbook for Enhancing EFL Learners' Public Speaking Skills in Islamic Higher Education - Purwati, Diana; Yasin, Ilyas; Mardiah, Ainol; Wulandari, Wulandari (FKIP - Universitas Riau, 2025)
Public speaking is an essential competence for EFL learners in Islamic higher education, particularly in related to English for Islamic Studies. However, EFL learners tend to pose psychological problems to enhance their public speaking. Traditional materials often fail to support students in overcoming speaking anxiety, enhancing fluency, and integrating Islamic perspectives into English learning. This study aims to develop and evaluate a digital flipbook as an innovative learning medium to enhance students’ public speaking skills. Using a Research and Development (R&D) design with the 4 D model, the study involved twenty seven students from one of rural islamic higher institutions. The digital flipbook was designed to integrate interactive content, Islamic values, and deep learning features to provide adaptive feedback. Validation by media and material experts indicated high feasibility (≥ 85%). Students’ public speaking performance, assessed through pre- and post-tests, showed significant improvement across fluency, vocabulary, pronunciation, and confidence. Furthermore, students reported positive perceptions of the flipbook, noting increased engagement, motivation, and alignment with their academic and religious needs. The findings highlight the potential of digital flipbooks to bridge technology and Islamic education, providing an effective tool to support EFL learners’ speaking development in Islamic higher education.